Five years' experience of combined intralesional therapy in infantile hemangioma - Ahmed Abdelghaffar Helal; Mohammad Alsayed Daboos (SpringerOpen, 2019)
Abstract Background Infantile hemangiomas (IHs) are common vascular tumors. Although it involutes spontaneously, outcomes are unpredictable. Intralesional therapy is one of its treatment modality. We present our experience with combined intralesional therapy for IHs over a 5-year duration. A total of 427 patients were treated and followed at Al-Azhar University Hospitals during the study period of 5 years. All patients were treated by intralesional therapy in the form of combined injection of triamcinolone and bleomycin. All patients were followed for the response. Response to the treatment was graded as marked, partial, and poor improvement. Results IHs were noticed within the first month of life in 90.2% of patients. The commonest site of involvement was head and neck in 90% of patients. The commonest clinical presentation was swelling with discoloration. Mean age was 7.43 ± 6.04 months and mean IHs size was 15.54 ± 11.13 cm2. The response to the treatment was highest for patients below 1 year of age. The reported complications were ulceration, scarring, and subcutaneous atrophy in some cases. Conclusion Combined intralesional therapy in IHs showed good efficacy in most patients. It is a reliable and safe treatment modality with clear curative effects and minimal complications. If IHs treatment is indicated, combined intralesional therapy should be considered as an alternative effective treatment modality.